Let C be the coefficient of x 2 in ( 1 − x ) ( 1 + 2 x ) ( 1 − 3 x ) ( 1 + 4 x ) ⋯ ( 1 + 1 4 x ) ( 1 − 1 5 x ) . Find ∣ C ∣ .
[2004 AIME 1 Problem 7]
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To get x 2 you multiply x terms from two factors and 1 s from other factors. Basically, we need to find all combinations of these x terms, calculate and sum them. There are ( 2 1 5 ) = 1 0 5 of them, but I decided to group them nicely according to the first term: all combinations with − x , then 2 x , − 3 x , and so on. Then I wrote a python code to do that faster for me, I hope it's understandable.
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 |
|
Let given expression 'E' c o f f e c i e n t o f x 2 = 2 1 l i m x ⟶ 0 { D ′ ′ ( E ) } = 5 8 8 w h e r e D ′ ′ ( E ) m e a n s d o u b l e d e r i v a t i v e o f E w i t h r e s p e c t t o x . NOTE: use logarithmic differentiation.(for easy calculation)
Can you please give explanation for what you have done ? Thanks.
Here is a non-calculus/non-programming partial solution.
I will give a recursive forumula without proof:
F n = F n − 1 − n ⌊ 2 n ⌋
By evaluating the first two products as ( 1 − x ) ( 1 + 2 x ) , the coefficient of x 2 is − 2 . So let F 2 = − 2 .
Applying the recursive formula until F 1 5 we get F 1 5 = 5 8 8 .
Mathematica:
Abs@Coefficient[Product[1 + (-1)^n*n*x, {n, 15}], x^2]
588
Let f ( x ) = ( 1 − x ) ( 1 + 2 x ) ( 1 − 3 x ) ( 1 + 4 x ) ⋯ ( 1 + 1 4 x ) ( 1 − 1 5 x ) . We need to find 2 ! f ′ ′ ( 0 ) = C and we have:
f ( x ) ⟹ f ( 0 ) f ′ ( x ) ⟹ f ′ ( 0 ) f ′ ′ ( x ) ⟹ f ′ ′ ( 0 ) ⟹ C ∣ C ∣ = k = 1 ∏ 1 5 ( 1 + ( − 1 ) k k x ) = 1 = k = 1 ∑ 1 5 1 + ( − 1 ) k k x ( − 1 ) k k f ( x ) = k = 1 ∑ 1 5 1 + ( − 1 ) k k ( 0 ) ( − 1 ) k k f ( 0 ) = k = 1 ∑ 1 5 ( − 1 ) k k = − 1 + 2 − 3 + 4 − 5 + 6 ⋯ − 1 3 + 1 4 − 1 5 = 1 + 1 + 1 + 1 + 1 + 1 + 1 − 1 5 = − 8 = k = 1 ∑ 1 5 ( 1 + ( − 1 ) k k x ) 2 ( − 1 ) k k ( f ′ ( x ) ( 1 + ( − 1 ) k k x ) − ( − 1 ) k k f ( x ) ) = k = 1 ∑ 1 5 ( ( − 1 ) k k ( − 8 ) − k 2 ) = − 8 k = 1 ∑ 1 5 ( − 1 ) k k − k = 1 ∑ 1 5 k 2 = − 8 ( − 8 ) − 6 1 5 ( 1 6 ) ( 3 1 ) = − 1 1 7 6 = − 2 1 1 7 6 = − 5 8 8 = 5 8 8
L e t a n = 1 + ( − 1 ) n ∗ n ∗ x . M a k e a n o t e : − I n a n ∗ a n + 1 t h e r e a r e n ∗ ( n + 1 ) − x 2 s . a n d n i s a n i n t e g e r . ∴ I n a n ∗ a n + 1 + a n ∗ a n + 2 = a n ∗ { a n + 1 ∗ a n + 2 } t h e r e i s o n l y 0 N E + x 2 . S o f o r e a c h a n , w e c a n m a k e a p a i r o f t w o a d j o i n i n g l i n k s , a r a n d a r + 1 , n < r < 1 6 , a n d w h o s e s u m w i l l h a v e o n l y o n e + x 2 . B u t f o r e v e n n a f t e r p a i r i n g − a 1 5 r e m a i n s , s o t h a t w i l l g e t n ∗ 1 5 − x 2 s i n i t . S o o u t o f t h e p a r i n g s , w e g e t n = 1 ∑ 1 5 n ∗ ⌊ 2 1 5 − n ⌋ = 2 5 2 o f + x 2 s . I n e v e n n = 2 m w i t h a 1 5 w e g e t m = 1 ∑ 7 2 ∗ m ∗ ( − 1 5 ) = 2 7 ∗ ( 7 + 1 ) ∗ 2 ∗ ( − 1 5 ) = 8 4 0 o f − x 2 s . S o ∣ C ∣ = ∣ + 2 5 2 − 8 4 0 ∣ = 8 4 0 − 2 5 2 = 5 8 8 E x p l a n a t i o n : − T a k e n = 6 . ( 1 + 6 x ) ( 1 − 7 x ) ( 1 + 8 x ) ( 1 − 9 x ) ( 1 + 1 0 x ) ( 1 − 1 1 x ) ( 1 + 1 2 x ) ( 1 − 1 3 x ) ( 1 + 1 4 x ) ( 1 − 1 5 x ) F o r x 2 : − ( 1 + 6 x ) ∗ { ( 1 − 7 x ) + ( 1 + 8 x ) + ( 1 − 9 x ) + ( 1 + 1 0 x ) + ( 1 − 1 1 x ) + ( 1 + 1 2 x ) + ( 1 − 1 3 x ) + ( 1 + 1 4 x ) + ( 1 − 1 5 x ) } . . . . . . . ⟹ + 6 x ∗ { − 7 x + 8 x + − 9 x + 1 0 x + − 1 1 x + 1 2 x + − 1 3 x + 1 4 x + − 1 5 x ) } . . . . . . . . . . . . . . . . . . . . + 6 x ∗ { + 1 x + 1 x + 1 x + 1 − 1 5 x ) } . . . . . . . . . . . . . . . . . . . . . . { + 6 ∗ ( 1 + 1 + 1 + 1 ) + 6 ∗ ( − 1 5 ) } ∗ x 2 . ( 2 4 − 9 0 ) ∗ x 2 . B y o u r f o r m u l a a b o v e : − . . n = 2 m . . . . . . . . . . . . . . . . . . . ( 2 m ∗ ⌊ 2 1 5 − n ⌋ n ∗ ( − 1 5 ) ) ∗ x 2 . . . . . . . . . . . . . . . . . . . . . . { 6 ∗ ⌊ 2 1 5 − 6 ⌋ 6 ∗ ( − 1 5 ) } ∗ x 2 ( 6 ∗ 4 − 9 0 ) ∗ x 2 .
Problem Loading...
Note Loading...
Set Loading...
Let y be the polynomial. Then ln ( y ) y y ′ = ln ( 1 − x ) + ln ( 1 + 2 x ) + ⋯ + ln ( 1 − 1 5 x ) = − 1 − x 1 + 1 + 2 x 2 − ⋯ − 1 − 1 5 x 1 5 . Plugging in x = 0 gives y = 1 and y ′ = − 1 + 2 − 3 + ⋯ + 1 4 − 1 5 = − 8 .
Taking one more derivative gives y 2 y ( y ′ ′ ) − ( y ′ ) 2 = − ( 1 − x ) 2 1 − ( 1 + 2 x ) 2 4 − ⋯ − ( 1 − 1 5 x ) 2 2 2 5 , so plugging in x = 0 as before gives y ′ ′ − ( − 8 ) 2 = − 1 − 4 − ⋯ − 2 2 5 , so y ′ ′ ( 0 ) = 6 4 − k = 1 ∑ 1 5 k 2 = 6 4 − 6 1 5 ( 1 6 ) ( 3 1 ) = 6 4 − 1 2 4 0 = − 1 1 7 6 . Now y ′ ′ ( 0 ) is just 2 C , so C = − 5 8 8 , and the answer is 5 8 8 .